Alcohol dehydrogenase 1C (ADH1C) gene polymorphism and alcoholic liver cirrhosis risk: a meta analysis - He, Lei (Int J Clin Exp Med, 2015)
The association between alcohol dehydrogenase 1C (ADH1C) gene polymorphism and alcoholic liver cirrhosis (ALC) has been analyzed in several studies, but results have been conflicting. In this study, a meta-analysis was performed to assess the associations between the ADH1C polymorphism and risk of ALC. Relevant studies were identified using PubMed, Web of Science, CNKI and Wanfang databases up to January 10, 2015. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the strength of the association using the fixed or random effect model. A total of 16 case-control studies, including 1375 cases and 1802 controls, were included. Overall, no significant association between the ADH1C polymorphism and ALC risk was found (dominant model: OR=0.87, 95% CI: 0.62-1.23; recessive model: OR=1.30, 95% CI: 0.84-1.99; *1/*2 vs. *1/*1: OR=0.87, 95% CI: 0.63-1.21; *2/*2 vs. *1/*1: OR=1.10, 95% CI: 0.71-1.70). In the subgroup analysis by ethnicity, we observed a significant association in Asian descent (*1/*2 vs. *1/*1: OR=1.63, 95% CI: 1.07-2.49), while a decreased risk was found among Caucasians (dominant model: OR=0.81, 95% CI: 0.66-0.99; *1/*2 vs. *1/*1: OR=0.76, 95% CI: 0.61-0.95). This meta-analysis demonstrated that the ADH1C polymorphism might increase the risk of ALC in Asians, while it may be a protective factor for ALC among Caucasians.